Correlação do teor de umidade com suas propriedades termofísicas em um meio poroso - Acerbi, Luisa Maria Caleiro (1995)
The knowledge of humidity in a médium is very important in many industrial process. The purpose of this study is to determine a correlation between moisture and thermophysical properties. In this work were constructed porous samples with diferent porosities that was submited to a thermal analysis. Thermal i characterization of this samples are obtained with the survey of the temperture profile through superficial and internai thermocouples and heat flux that cross the médium. The thermophysical properties are obtained by parameter estimation technique in the time domain. The proposed correlation allows both a vision quantitative and qualitativity of the saturation influence and porosity in the thermophysical properties.